GAME ONLINE SEBAGAI POLA PERILAKU: Studi Pada Mahasiswa Ilmu Komunikasi Universitas Tadulako - Muhammad Wahid; Ahmad Fauzan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
The development of this technology has a big influence on its users, especially with the emergence of online gaming applications in smartphones. Gameonline is one of the things that are popular among gadget users, this can be seen with the emergence of various types of online games on the smartphone. With the presence of online games and excessive use will cause concern, especially on changes in attitudes and behavior patterns of its users. This research aims to find out and provide an overview of how the behavior patterns of Untad communication science students in doing activities to play Gameonline. Research methods use qualitative methods. Data collection techniques are in observations and depth interviews. The results showed that the behavior patterns of gameonline users showed significant changes, behavior patterns formed provided changes that are different from the previous one. Of course, this change in behavior patterns when they have known and started addicted to playing online games so that the changes that appear to change their daily habits.